VIRTUAL REALITY BERBASIS COGNITIVE BEHAVIOR THERAPY UNTUK MENURUNKAN KECEMASAN BERBICARA DI DEPAN UMUM - Eliza Sutri Utami; Fidia Oktarisa (LP2M IAI Al Khairat Pamekasan, 2021)
Most students carry out formal communication such as presenting assignments or expressing opinions in formal forums and there is anxiety about public speaking in their implementation. Virtual reality based on cognitive behavior therapy (VR-CBT) is one of the psychological interventions that can be applied in this study with the aim of reducing the level of anxiety in public speaking. The public speaking anxiety scale, TMAS, and psychological tests were used as measures to determine the subject's anxiety level. Collecting data using observation and interviews with subjects and related parties. This research design uses descriptive qualitative with a case study approach (case study). This study consisted of one subject who was a 20 year old sixth semester student. The VR CBT consisted of 10 sessions (+60 minutes / session). The data analysis technique used qualitative data analysis. The results showed that the subject's public speaking anxiety level decreased. That is, VR CBT is effective in reducing the level of public speaking anxiety.